Rangīn kamān-i shiʻr : taẕkarahʹī az sukhanvarān-i Fāryāb : az qarn-i yāzdahum ilá nīmah-ʼi avval-i qarn-i chahārdahum - Gudāz, Muḥammad Aslam ([s.n.], 1990)
Selected poems of the poets from Fāryāb Province, Afghanistan; includes their short biographical sketches.